Determinants of Mortality Among Severely Malnourished Children in Northern Nigeria - Shafique Sani Nass; Nafisa Sani Nass; Zubairu Iliyasu; Bello Suleiman; Shamsuddeen Yahaya; Bala Habibu; Murtala Isa Bindawa; Aminu Sani; Medinat Suleiman; Adamu Suleiman Gachi (SAGE Publishing, 2021)
Objectives Severe Acute Malnutrition is a significant cause of mortality in children under the age of 5 years in low-resource settings, including Northern Nigeria. The study aimed to determine the associations between selected risk factors and mortality outcomes in children admitted with SAM in a facility in Katsina State, Northern Nigeria. Methods A prospective observational cohort of 201 children aged 6 to 59 months who were admitted with severe acute malnutrition (SAM) in stabilization centers in Katsina State, Northern Nigeria between May 18, 2021, and July 20, 2021, (63 days) were assessed followed up. Outcomes were analyzed using Kaplan-Meir analysis to estimate time to death, and Cox proportional-hazard regression model was used to determine predictors of mortality. Results The log-rank test showed significant differences in the probability of death between categories of diarrheal status (log-rank statistic = 9.760, P  = .021) and presence of existing disease (comorbidity) (log-rank statistic = 5.338, P  = .021). The study identified that severely malnourished children admitted with comorbidities showed significant association with time to event (death) (AHR: 4.109, 95% CI: 1.51, 32.60). The estimated mean time until death was 57.9 days (±3.0) for children without comorbidities and 20.1 (±3.0) days for children with comorbidities. The median survival time was 18 days for children with comorbidities. Conclusion The presence of comorbidities was significantly associated with mortality. Severely malnourished children with comorbidities had 4 times higher mortality risk than severely malnourished children admitted without comorbidities. Clinicians and health workers should give due emphasis to the early detection and effective management of comorbidities in children with severe acute malnutrition.